2016
DOI: 10.14393/bj-v32n1a2016-29745
|View full text |Cite
|
Sign up to set email alerts
|

Penetration resistance and density of a yellow oxissol under conventional management at different ages

Abstract: RESUMO:Brazilian agriculture has been highlighted in Savanna areas due to significant gains in production and productivity in this biome. However, the production model with intensive use of machines for several years causes drastic changes in soil physical quality. This study aimed to investigate the influence of conventional management adoption time in a Yellow Oxissol on soil physical properties. Soil density, particle density, total porosity and soil resistance to penetration were assessed in areas under co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Soil preparation is an important component, because it influences the attributes that determine the physical quality of the soil and act on its structure. The agricultural exploitation of these areas with soybean cultivars is based on management systems with intense soil disturbances due to plowing and harrowing, thus modifying the soil's original characteristics (Barbosa et al, 2016). Prolonged conventional management systems leave the latosols exposed and cause the disintegration of macroaggregates, resulting in rapid decomposition of organic matter (Ibiapina et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Soil preparation is an important component, because it influences the attributes that determine the physical quality of the soil and act on its structure. The agricultural exploitation of these areas with soybean cultivars is based on management systems with intense soil disturbances due to plowing and harrowing, thus modifying the soil's original characteristics (Barbosa et al, 2016). Prolonged conventional management systems leave the latosols exposed and cause the disintegration of macroaggregates, resulting in rapid decomposition of organic matter (Ibiapina et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The highest values of total porosity (TP) in the depths studied were observed in the NV and CS2 areas. Barbosa et al (2016), who studied the chronosequence of conventional management in soybean crops, also found higher TP in newly explored areas under native vegetation, compared to areas with longer management time. In relation to areas with a longer history of management, the result observed for ESC in the superficial layer indicates that scarification can be an alternative to improve the porosity of a soil that has been managed for a certain time in a conventional manner.…”
Section: Resultsmentioning
confidence: 82%
“…The climate, according to the Köppen climate classification, is of the type Aw'. The soil is classified as Yellow Latosol (Barbosa et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…These results are in consonance with the findings of Neves Neto et al (2012), who studying the physical and chemical changes of a dystrophic Yellow Oxisol caused by the replacement of the native forest with Mombasa grass, observed that three years after grass introduction, the soil already presented a significant reduction of PT and an increase in DS levels. Lepsch (2011) argues that DS and PT are closely related attributes, since they deal with the relationship between the arrangement of the solid particles of the soil and, therefore, are sensitive attributes, capable of differentiating management systems or even the time in use of a given system (Barbosa et al, 2016, Reicherdt et al, 2007, and they behave in an inversely proportional manner: the lower PT values, the higher the DS values. Spera et al (2009), when assessing integration systems, found PT values very close to those under the native forest system.…”
Section: Soil Water Retention Curvesmentioning
confidence: 99%